(untitled) (Journal of Universal Science Research, 2024)
Due to the fact that in order to ensure the movement of a walking robot it is necessary to solve the problem of maintaining balance, there is a need to develop a kinematic diagram of the robot, and also to decide how the resulting tilts, rotations and vibrations will be compensated. This article presents the development of a kinematic diagram of a bipedal walking robot. In this robot, arm movements will compensate for unbalancing leg movements.